The unruly notion of abuse of rights / Jan Paulsson. - Paulsson, Jan (Cambridge University Press, 2020)
Everyone condemns what they perceive as 'abuse of rights', and some would elevate it to a general principle of law. But the notion seldom suffices to be applied as a rule of decision. When adjudicators purport to do so they expose themselves to charges of unpredictability, if not arbitrariness. After examining the dissimilar origins and justification of the notion in national and international doctrine, and the difficulty of its application in both comparative and international law, this book concludes that except when given context as part of a lex specialis, it is too nebulous to serve as a general principle of international law.